Development macroeconomics - Agenor Pierre-Richard; Montiel Peter J (Princeton Princeton Univ Press, 1999)
This new edition is centered on the analytic foundations of macroeconomic policy formulation. It emphasizes the interaction between macroeconomic policies and long term growth, the political economy of macroeconomic reform, the management of capital infl
Keywords: Developing countries; Development economics; Economic conditions; Macroeconomics